Ochratoxin A occurrence, its pathological effects on poultry health and decontamination approaches - MEHTAB, U; TAHIR, MA; ABBAS, RZ; ABBAS, A; HUSSAIN, K; SIDDIQUI, F; MOHSIN, M; RANI, Z; REHMAN, A; YASIN, R (Journal of the Hellenic Veterinary Medical Society, 2022)
Mycotoxins are filamentous fungi which can be seen microscopically and they impart adverse effects on poultry health. The occurrence of mycotoxins in poultry feed imparts adverse effects not only to the birds’ health but also causes huge economic losses by affecting feed conversion ratio, production of meat and eggs,and also responsible for histopathological changes in lymphoid organs of chicken. More than 300 different species of mycotoxins have been reported from which the ochratoxin and aflatoxins are the most harmful for poultry industry. Among ochratoxins, especially the Ochratoxin A (OTA) is produced from Aspergillus Ochraceus and and Penicillium verrucosum species as storage fungi inside stored drains and feed ingredients. The ochratoxicity is a dose-dependent factor and hits the immune system of birds besides decreased feed intake and decreased body weight. Higher doses of OTA toxicity resulted in deterioration of egg shell quality and hatchability in layers and breeders. Histopathological profile of ochratoxicity affected birds showed severe to moderate changes in the kidney, bursa of Fabricius, liver, thymus, spleen, heart, and lungs depending on dosage. In this review article, an attempt has been made to concise the OTA associated alterations in growth pattern, production index, biochemical changes and histopathological profile of the poultry. The current approaches and agents (Vitamin-E, Silymarin), which are being used to reduce the effects of OTA toxicity in birds, have also been discussed.